2013
DOI: 10.1175/bams-d-11-00043.1
|View full text |Cite
|
Sign up to set email alerts
|

Revolutionizing Climate Modeling with Project Athena: A Multi-Institutional, International Collaboration

Abstract: The importance of using dedicated high-end computing resources to enable high spatial resolution in global climate models and advance knowledge of the climate system has been evaluated in an international collaboration called Project Athena. Inspired by the World Modeling Summit of 2008 and made possible by the availability of dedicated high-end computing resources provided by the National Science Foundation from October 2009 through March 2010, Project Athena demonstrated the sensitivity of climate simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 40 publications
3
84
0
1
Order By: Relevance
“…Studies have suggested that dynamical downscaling of bias-corrected (as opposed to raw) GCM output does offer improvements in fidelity when reproducing historical climate (43,44). Some authors have also suggested that using high-resolution GCMs could reduce some of the large-scale biases seen in coarser model output (45). To date, no studies have evaluated the consequences in an impacts model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that dynamical downscaling of bias-corrected (as opposed to raw) GCM output does offer improvements in fidelity when reproducing historical climate (43,44). Some authors have also suggested that using high-resolution GCMs could reduce some of the large-scale biases seen in coarser model output (45). To date, no studies have evaluated the consequences in an impacts model.…”
Section: Discussionmentioning
confidence: 99%
“…For example, due to the local Rossby radius of deformation a 1/3 • resolution ocean model cannot resolve the most important processes, eddies, while at 60 km the atmosphere can Shaffrey et al, 2009;Demory et al, 2014). Coarse-resolution simulations can produce representative data for global mean properties, but their limitations for studying regional effects and temporal variability are becoming more obvious Shaffrey et al, 2009;Scaife et al, 2011;Delworth et al, 2012;Kinter et al, 2013). Recent work by Demory et al (2014) demonstrates that the energy budgets in an ensemble of different resolution versions of the HadGEM3 (Hadley Centre Global Environment Model 3) and HadGEM1 are very consistent, but moisture transport and the balance of evaporation and precipitation over land, critically important for climate impacts, only converges at resolutions finer than 60 km (N216 and above).…”
Section: Introductionmentioning
confidence: 99%
“…the European Union's Horizon 2020 PRIMAVERA project, https://www.primavera-h2020.eu/). In particular this study complements groundbreaking past initiatives in pioneering the use of HPC (high-performance Computing) for climate simulations such as the UPSCALE and the ATHENA (Kinter III et al, 2013) projects.…”
Section: Introductionmentioning
confidence: 71%
“…Each deterministic experiment included in Climate SPHINX has a counterpart where the sub-grid unresolved scales have been parameterised with two different stochastic physics schemes (namely the SPPT and SKEB schemes). This makes Climate SPHINX the first climate dataset that includes a large number of ensemble members with a stochastic parameterisation at different horizontal resolution; along with other high-resolution simulation campaigns such as UP-SCALE or ATHENA (Kinter III et al, 2013), this demonstrates the ability of the climate community to exploit the more recent HPC machines.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation